2022
DOI: 10.3897/zookeys.1081.63009
|View full text |Cite
|
Sign up to set email alerts
|

A new rainfrog of the genus Pristimantis (Anura, Brachycephaloidea) from central and eastern Panama

Abstract: Substantial molecular and morphological character differences lead us to the description of a new species of the genus Pristimantis from the cloud forest of Cerro Chucantí, Maje Mountains, Darien Province, as well as from several other mountain ranges in eastern and central Panama. Pristimantis gretathunbergaesp. nov. is a sister species to the allopatric P. erythropleura-penelopus group from northern Colombia with a mtDNA sequence divergence of > 4.4% at 16S and > 14.6% at COI. Its closest conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Besides nest‐building activities, there are species with direct development where either the female (e.g. Chinchilla‐Lemus & Meneses‐Pelayo, 2016 ; Mebert et al., 2022 ; Ortega‐Andrade et al., 2010 ; Pombal et al., 1994 ) or the male (e.g. Bignotte‐Giró et al., 2022 ; Chinchilla‐Lemus & Meneses‐Pelayo, 2016 ; Mebert et al., 2022 ; Rojas‐Rivera et al., 2013 ) care for the recently laid eggs, and in some cases, parents of these species carry newly hatched froglets over several weeks on their backs to provide protection (Diesel et al., 1995 ; Schulte et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides nest‐building activities, there are species with direct development where either the female (e.g. Chinchilla‐Lemus & Meneses‐Pelayo, 2016 ; Mebert et al., 2022 ; Ortega‐Andrade et al., 2010 ; Pombal et al., 1994 ) or the male (e.g. Bignotte‐Giró et al., 2022 ; Chinchilla‐Lemus & Meneses‐Pelayo, 2016 ; Mebert et al., 2022 ; Rojas‐Rivera et al., 2013 ) care for the recently laid eggs, and in some cases, parents of these species carry newly hatched froglets over several weeks on their backs to provide protection (Diesel et al., 1995 ; Schulte et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chinchilla‐Lemus & Meneses‐Pelayo, 2016 ; Mebert et al., 2022 ; Ortega‐Andrade et al., 2010 ; Pombal et al., 1994 ) or the male (e.g. Bignotte‐Giró et al., 2022 ; Chinchilla‐Lemus & Meneses‐Pelayo, 2016 ; Mebert et al., 2022 ; Rojas‐Rivera et al., 2013 ) care for the recently laid eggs, and in some cases, parents of these species carry newly hatched froglets over several weeks on their backs to provide protection (Diesel et al., 1995 ; Schulte et al., 2020 ). All these examples, including the observation presented in the present report, suggest that highly specialized forms of parental care may be adaptive in direct developing species.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the naming of species for celebrities [24] seems like a strategy tailor-made for generating public attention to species discovery. Eponymous names have been coined for musicians (the fern Gaga monstraparva [74]), actors (the beetle Agra katewinsletae [75]), filmmakers (the alga Euthora timburtonii [76]), athletes (the wasp Diolchogaster ichiroi [77]), politicians (the lichen Ocellularia jacinda-arderniae [78]), activists (the frog Pristimantis gretathunbergae [79]), novelists (the fossil sea turtle Psephophorus terrypratchetti [80]) and more. Blake et al [81] have shown that species with such names attract more Wikipedia page views than their close relatives with non-celebrity names-with the effect being especially strong in less charismatic taxa such as invertebrates and amphibians, and weaker to undetectable for birds and mammals.…”
Section: (B) Scientific Naming and Public Attention To Sciencementioning
confidence: 99%
“…In particular, the naming of species for celebrities [ 24 ] seems like a strategy tailor-made for generating public attention to species discovery. Eponymous names have been coined for musicians (the fern Gaga monstraparva [ 74 ]), actors (the beetle Agra katewinsletae [ 75 ]), filmmakers (the alga Euthora timburtonii [ 76 ]), athletes (the wasp Diolchogaster ichiroi [ 77 ]), politicians (the lichen Ocellularia jacinda-arderniae [ 78 ]), activists (the frog Pristimantis gretathunbergae [ 79 ]), novelists (the fossil sea turtle Psephophorus terrypratchetti [ 80 ]) and more. Blake et al .…”
Section: When Creativity Shapes Sciencementioning
confidence: 99%